Prevalence and Severity of Visual Impairment in patients with Diabetic Foot Sepsis presenting in Surgical OPD of a Tertiary Care Hospital: An Observational Study - Muhammad Zafar Iqbal, Malik Irfan Ahmed, Abdul Qadir Khurrum, Samra Riaz, Ali Kamran (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Amongst various complications of Diabetes mellitus, Diabetic septic foot and visual pathologies are most dreadful complications that lead to physical disability. Both of these conditions are due to Microvascular and Macrovascular pathology. Both of these conditions are well researched independently, but their specific co relationship between advance DSF and Ocular morbidity in Pakistani public remains under explored. Objective: To determine the prevalence and severity of Diabetic Retinopathy and other visual pathologies in patients with Diabetic Septic Foot (DSF) disease, presenting daily Surgery Outpatients Department (OPD), in allied hospitals. Methods: This prospective (cross sectional) study was conducted at Allied Hospitals of Rawalpindi Medical University from March 2019 to March 2023. A total of 315 patients were enrolled who had clinical DSF disease. The patients were examined by surgical specialist and findings noted on a Performa. These patients were then sent to Ophthalmology OPD with the same Performa. The ophthalmologist performed their relevant test which included visual acuity, slit-lamp examination, and fundoscopy through dilated pupils. The combine data both from general surgical and Ophthalmology specialists were analyzed using SPSS version 26. Results: The study analyzed data from 315 patients with diabetic septic foot disease. The cohort had a mean age of 52.1 +- 8.4 years, with half of the patients (50.5%, n=159) belonging to the 40-50 years age group. This indicates a high disease burden in economically productive population. There was a significant male predominance (82.2% , n=259). A large proportion of patients were not well educated, with 51.7% ( n=163) educated bellow middle standard and 14.0% (n=44) being illiterate. The mean duration of diabetes was 10.2 +- 4.8 years. Regarding foot pathology, a very large number (42.5%, n=134) of patients presented with gangrene, needing major or minor amputation of part involved. According to wageners classification, a significantly large number (n=234 ) of patients had advance DSF disease on presentation ( grade 3,4,and 5). Ophthalmologic findings: The comprehensive examination of both eyes of patients revealed a staggering burden of ocular morbidity. The most significant finding was that 55 % of the patients (n=175 ) had some degree of diabetic retinopathy. The severity was distributed across the spectrum, with 17.8% (n=56) having mild non-proliferative DR (NPDR), 34.0 %(n=107) had moderate to severe NPDR, and 12.0 % ( n=12) had sight threatening proliferative DR(PDR). A vast majority of patients (84.1%, n=265) had correctable refractive errors. Cataract was present in 55.6% ( n=175) of cohort of patients. A cross tabulation analysis revealed a statistically significant association ( p< 0.001) between the severity of DSF disease and stage of DR. Conclusion: this study revealed an alarming high prevalence of Diabetic Retinopathy in patients of DSF presenting in surgical OPDs of Aliied Hospitals of Rawalpindi Medical University. The triad of low socioeconomic status, poor glycemic control and delayed presentation leads to concurrent, severe microvascular and macrovascular complications, which result in limb or foot disasters. These findings mandate an integrated , multidisciplinary care model in our settings for the management of Diabetic Septic foot. This will facilitate early detection and management of DSF. This is the only way to prevent catastrophy related to lower limbs of Diabetic patients. Keywords: diabetic septic foot, Diabetic Retinopathy, diabetic complications, multi-disciplinary, multi-disciplinary care.